Pengaruh Orientasi Kewirausahan dan Orientasi Pasar terhadap Keunggulan Bersaing pada UMKM di Kawasan M.Said - Hermayanti, Anggun -; Rahayu, Vitria Puri; Sutrisno, Sutrisno (Peneliti.net, 2024)
UMKM in the M.Said area face very tight competition. Where business actors run their businesses very close together and have similar businesses. So the high level of competition requires business actors to have a competitive advantage. Apart from that, business actors must also have strategies to use, namely entrepreneurial orientation and market orientation. The aim of this research is to determine the influence of entrepreneurial orientation and market orientation on the competitive advantage of UMKM in the M.Said area. This research uses a quantitative type of research, based on the results of research conducted by distributing questionnaires to 86 UMKM in the M.Said area. The data analysis techniques used in this research are classical assumption testing, multiple linear regression analysis, hypothesis testing, and coefficient of determination. The research results show that there is no partial influence of entrepreneurial orientation on competitive advantage with a calculated t value of 0.971 < t table 1.988 and a significance value of 0.334 > 0.05, so that entrepreneurial orientation has not been able to increase the competitive advantage of UMKM in the M.Said area. Meanwhile, market orientation has a partial influence on the competitive advantage of UMKM in the M. Said area, with a calculated t value of 3.064 < t table 1.988 and a significance value of 0.003 > 0.05, so that market orientation is able to increase competitive advantage whose influence lies in customer orientation. However, there is a simultaneous influence of entrepreneurial orientation and market orientation on competitive advantage in UMKM in the M.Said area, with a significance value of 0.002 < 0.05 and F count 6.940 > 3.10 F table, so that entrepreneurial orientation partially has no effect on excellence compete while market orientation partially has a high level of influence on competitive advantage